Library Architecture: Some Observations - Fabian, Bernhard (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
There are plenty of libraries (among them many university and research libraries) which do not provide adequate work-places. Chairs may have been selected for their stylish look rather than for their physical comfort. Desk lamps may have been deemed unnecessary (they might have distorted the overall impression which the reading room was expected to make) And so on. I keep wondering how many librarians have spent some time in their libraries as readers, and have assessed their reading rooms from the user’s point of view. Have they been in a cubicle? Or have they read a book under glaring neon lights? Do they know how well their air-conditioning works? I know a library in which the only window that can be opened is in the librarian’s office.